Code-Switching and Mixed Morphology in Multilingual Social Media a Thematic NVivo Analysis - Masniati, Andi; Alwiyah, Tuti; Margana; M, Muhammad; Rumbia, Aidin; Henaulu, Alfan; Rusdi Badri, Amal (Institut Agama Islam Negeri Parepare, 2026)
This study aims to analyze code-switching practices and mixed morphology in social media communication and to reveal users’ social motives and linguistic awareness toward this phenomenon. The study employs a descriptive qualitative approach, with data collected through documentation of social media posts, observation, and semi-structured interviews with purposively selected informants. The data were analyzed using NVivo 12+ software through the stages of open coding, axial coding, and selective coding to map linguistic patterns and social themes. The results indicate that intra-sentential code-switching is the most dominant form, accompanied by a high productivity of mixed morphology in the form of Indonesian affixation attached to English base words, such as in the forms di-upload, nge-like, and ke-cancelan. The findings also reveal that the use of mixed language is influenced by stylistic factors, digital identity, communication efficiency, and audience adaptation strategies, while awareness of the impact of language use on the sustainability of local languages remains relatively low.